Implementation of Fulfillment of the Right to Population and Civil Registration Administration Services for Persons with Disabilities - Setiawan, Arvan; Nukyanto, Damainsa Prahesti; Yanuaryta, Elok Izra; Fitria, Mirza Nur (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2024)
This study examines the implementation of civil registration services for people with disabilities in Solok District, Indonesia, highlighting the government's role in addressing barriers. Using a descriptive qualitative approach and Grindle's framework, it identified challenges like the lack of local regulations, stigma, low awareness, and inaccessible services. Despite these issues, positive outcomes were observed, with improved data collection and benefits for people with disabilities. A key finding is the importance of adequate budget allocation for successful implementation. The study's limitations include a short research period and limited budget, with future research recommending longer studies and broader comparisons.